2015
DOI: 10.14814/phy2.12608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epimuscular myofascial force transmission on sarcomere length of passive muscles in the rat hindlimb

Abstract: Results from imaging studies and finite element models suggest epimuscular myofascial effects on sarcomere lengths in series within muscle fibers. However, experimental evidence is lacking. We evaluated epimuscular myofascial effects on (1) muscle belly, fiber, and mean sarcomere length and (2) sarcomere length distribution within passive fibers of the rat tibialis anterior (TA) and soleus (SO) muscles. Hindlimbs (n = 24) were positioned in predefined knee (55°, 90°, 125°, 160°) and ankle (either 90° or 125°) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
1
25
1
Order By: Relevance
“…It is important to note that the one-joint muscle was active in the present study and passive in the imaging studies. Recently, we also found effects of epimuscular myofascial force transmission on the distribution of sarcomere lengths within a passive TA in rats (Tijs et al, 2015b), while no effects on the joint moment exerted by TA were found in the present study. This suggests that effects of epimuscular myofascial force transmission that occur in passive muscle conditions do not necessarily have the same impact in active muscle conditions.…”
Section: Effects Of Epimuscular Myofascial Connections On Ta and Edlcontrasting
confidence: 47%
“…It is important to note that the one-joint muscle was active in the present study and passive in the imaging studies. Recently, we also found effects of epimuscular myofascial force transmission on the distribution of sarcomere lengths within a passive TA in rats (Tijs et al, 2015b), while no effects on the joint moment exerted by TA were found in the present study. This suggests that effects of epimuscular myofascial force transmission that occur in passive muscle conditions do not necessarily have the same impact in active muscle conditions.…”
Section: Effects Of Epimuscular Myofascial Connections On Ta and Edlcontrasting
confidence: 47%
“…6A). However, in the study by Bernabei et al (2015), both muscles were maximally activated, while the extent of mechanical interaction has been shown to decrease with submaximal activation and passive muscle conditions (Tijs et al, 2015a(Tijs et al, , 2016a. Moreover, the maximal MTU relative displacement imposed in the study by Bernabei et al LG proximal tendon is detached from its origin on the lateral epicondyle of the femur to show the intermuscular connective tissues and SO muscle belly lying more anterior in the triceps surae compartment.…”
Section: Mechanical Consequences Of Displacements Between Neighboringmentioning
confidence: 85%
“…2008; Maas and Sandercock 2008; Tijs et al. 2015b), imaging studies in humans do imply relevant effects (Bojsen-Moller et al. 2010; Huijing et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Tijs et al. 2015b), we assumed that muscle relative position was the sole determinant of force changes in the muscle group. In fact, these local effects occur as a consequence of changes in the imposed relative positions, so that relative position was selected as a global descriptor of length changes for the whole mechanical chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation